PROGRAM PENDIDIKAN PROFESI ARSITEK (Sebuah Tanggapan akan diberlakukannya Pendidikan Profesi Arsitek, sebagai pendidikan tambahan bagi lulusan program Strata 1 Arsitektur untuk berprofesi sebagai ARSITEK) - DJOKO PRATIKTO (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2008)
To work professionally a graduate of the .scholar SI Architecture still could not be carried out or was not yet acknowledged by the world community of the practice of architecture, except for this graduate has been experienced for 3 years in architeceure, or beforehand had wrought/the apprentice in the Consultant's company Architecture or through professional education architecture that was held by the educational agency or the organisation of the profession. This reality could be seen in the condition to memilki the professional certificate of the architect's expertise that was issued by the organisation of the Association of the Indonesian Architect (IAI) and the Development Agency of the Construction Service that is the Architect's certificate request